Rapidly Increasing Artificial Iodine Highlights Pathways of Iceland-Scotland Overflow Water and Labrador Sea Water - Castrillejo, Maxi; Casacuberta, Núria; Vockenhuber, Christof; Lherminier, Pascale (Frontiers in Marine Science, 2022)
Iceland-Scotland Overflow Water (ISOW) and Labrador Seawater (LSW) are major water masses of the lower Atlantic Meridional Overturning Circulation (AMOC). Therefore, the investigation of their transport pathways is important to understand the structure of the AMOC and how climate properties are exported from the North Atlantic to lower latitudes. There is growing evidence from Lagrangian model simulations and observations that ISOW and LSW detach from boundary currents and spread off-boundary, into the basin interior in the Atlantic Ocean. Nuclear fuel reprocessing facilities of Sellafield and La Hague have been releasing artificial iodine (129I) into the northeastern Atlantic since the 1960ies. As a result, 129I is supplied from north of the Greenland-Scotland passages into the subpolar region labelling waters of the southward flowing lower AMOC. To explore the potential of 129I as tracer of boundary and interior ISOW and LSW transport pathways, we analyzed the tracer concentrations in seawater collected during four oceanographic cruises in the subpolar and subtropical North Atlantic regions between 2017 and 2019. The new tracer observations showed that deep tracer maxima highlighted the spreading of ISOW along the flanks of Reykjanes Ridge, across fracture zones and into the eastern subpolar North Atlantic supporting recent Lagrangian studies. Further, we found that 129I is intruding the Atlantic Ocean at unprecedented rate and labelling much larger extensions and water masses than in the recent past. This has enabled the use of 129I for other purposes aside from tracing ISOW. For example, increasing tracer levels allowed us to differentiate between newly formed 129I-rich LSW and older vintages poorer in 129I content. Further, 129I concentration maxima at intermediate depths could be used to track the spreading of LSW beyond the subpolar region and far into subtropical seas near Bermuda. Considering that 129I releases from Sellafield and La Hague have increased or levelled off during the last decades, it is very likely that the tracer invasion will continue providing new tracing opportunities for 129I in the near future.